Investigating the Influence of Animation on the Iraqi Muslim Children in Iraq (Doctrinal, Social, Ethical, Academic Sides) (Journal of the College of Basic Education, 2024)
This study is to investigate the nature of animation's effect in doctrinal, social, ethical and academic sides as well as the views of Iraqi Muslim students, teachers and parents toward its influence. In this study, three hypotheses have been developed. A questionnaire has been formed and will be given to the chosen sample of two hundred Baghdad primary school students in the academic year 2023–2024 as well as teachers and parents in order to accomplish the objectives. The results show that parents and children both agree that animations have a negative effects on children's development. It is recommended that parents intentionally try to notice the animations their children are viewing to make sure it is suitable for their age and Islamic believes.